2002
DOI: 10.1055/s-2002-36717
|View full text |Cite
|
Sign up to set email alerts
|

Radiology of Osteoporosis

Abstract: Osteoporosis is a common metabolic bone disorder that may be broadly subdivided into generalized or regional osteoporosis. This article reviews the common causes of generalized osteoporosis with emphasis on the radiological appearances, complications, and differential diagnosis. The more important causes of regional osteoporosis such as disuse osteoporosis, reflex sympathetic dystrophy, and transient regional osteoporosis are also discussed, and their imaging features are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…One reason for this may be that bone absorption in the endosteum prevailed over osteogenesis in the periosteum post-ovariectomy. The characteristics demonstrated were similar to the ‘pencil line’ or ‘picture-framing’ sign of the human vertebrae in postmenopausal osteoporosis, which indicates cortical thinning (34). This finding demonstrated that the CRT-THK-C and CRT_DEN values of lumbar vertebrae may be effective markers in the OVX rat model of osteoporosis when ovariectomy is performed <180 days prior and may be used as reliable indices for evaluating drug effects.…”
Section: Discussionmentioning
confidence: 68%
“…One reason for this may be that bone absorption in the endosteum prevailed over osteogenesis in the periosteum post-ovariectomy. The characteristics demonstrated were similar to the ‘pencil line’ or ‘picture-framing’ sign of the human vertebrae in postmenopausal osteoporosis, which indicates cortical thinning (34). This finding demonstrated that the CRT-THK-C and CRT_DEN values of lumbar vertebrae may be effective markers in the OVX rat model of osteoporosis when ovariectomy is performed <180 days prior and may be used as reliable indices for evaluating drug effects.…”
Section: Discussionmentioning
confidence: 68%
“…Changes in bone density do not become evident on standard radiograms until a certain amount of bone mass is loss (estimated around 30%). Findings can be better appreciated in the axial skeleton and at the proximal portion of long bones and consist in increased bone radiolucency, changes of trabecular pattern network (at the beginning resorption involves mainly the horizontal trabeculae with relative accentuation of vertical ones, in later stages resorption extends also to the vertical trabeculae) and cortical thinning (4,45). These features may be better evaluated with CT scan.…”
Section: Qualitative Evaluationmentioning
confidence: 99%
“…As previous stated, vertebral fractures may at first be assessed with lateral conventional radiology and be described according to Genant's. On anteroposterior projection, the fracture is usually symmetrical on both sides; the integrity of the posterior must be also checked, for it is lost it may be a sign of malignancy (4,45) and need further investigations. A characteristic vertebral fracture sign, which is strongly indicative of compression fractures, is the Kümmel phenomenon, that represents the avascular necrosis of the collapsed vertebral body and appears as intravertebral vacuum on X-ray images (46), while on MRI has a fluid signal (47).…”
Section: Qualitative Evaluationmentioning
confidence: 99%
“…5,6 Osteoporosis, which is considered a ''silent disease'' until a fracture occurs, is associated with impaired bone strength, 7,8 which is influenced by a variety of factors 9 but strongly correlates with bone mineral density (BMD). [10][11][12][13][14][15] It is well established that structurally insufficient osteoporotic bone is predisposed to fracture [16][17][18] and that BMD can affect fracture stability after osteoporotic fractures. Patients with osteoporosis have an increased frequency of early instability, malunion, and late carpal malalignment compared to those with normal BMD.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that structurally insufficient osteoporotic bone is predisposed to fracture 16 -18 and that BMD can affect fracture stability after osteoporotic fractures. Patients with osteoporosis have an increased frequency of early instability, malunion, and late carpal malalignment compared to those with normal BMD.…”
Section: Introductionmentioning
confidence: 99%